On the Preferred Creditor Status of Multilateral Development Banks - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2023)
The loans of the IMF, World Bank, and other multilateral development banks (MDBs) are excluded from debt restructuring. This is the result of their preferred creditor status. There are two justifications for the preferred creditor status of MDBs: (a) they give concessional loans, and (b) they give loans to debt-distressed countries when other lenders would not. In this note, I present a conceptual framework that quantifies the benefit in case (b), discard the preferred creditor status of MDBs, and outline a debt restructuring process that includes MDBs. I also discuss a similar approach by Diwan, Harnoys-Vannier, and Kessler (2023), which also includes MDBs in debt restructuring but quantifies the benefit in case (a).
Keywords: H63; E62; 330; concessional loan; debt restructuring; haircut; multilateral development banks